Contemporary Southeast Asia security complex. - Nguyen, Nam Duong. (2008)
The dynamics and structure of the contemporary SEA security complex and the dominant patterns of security interaction in SEA after the Cambodian conflict. Regional security complex is structured around a pattern of security interaction between the mainland group (new ASEAN members) and the maritime group (original ASEAN members).